Dinamika dan Struktur Pendapatan Rumah Tangga Perdesaan di Berbagai Agroekosistem di Indonesia - Sri Hery Susilowati; Erma Suryani; Iwan Setiajie Anugrah; Fajri Shoutun Nida; Achmad Suryana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2020)
Agricultural development has an impact on the structural changes of the rural economy, as reflected in the changes of household income. The changes reflects the agricultural transformation which the direction and magnitude vary among ecosystems. Objective of this research was to analyze the dynamics of household income structure based on land tenure and agroecosystem. The study used panel data of Patanas (2007-2018) in eight provinces with three points of observation. Data was analized using the statistics and qualitative descriptive methods. Results of this study showed that household income, share of agriculture to total household income, and income structure changes were influenced by agroecosystem and land tenure. The largest income inequality was found in the vegetable dryland agroecosystems. Based on this study, it is recommended that to increase rural households’ income in each agroecosystem, among others, are through infrastructure development to facilitate the flow of agricultural products to the markets, employment creation through development of small and medium scales of agricultural based industry in the rural region, and increasing rural workforce skills to improve their access on employment opportunities in the agricultural and non-agricultural sector.